Occurrence of musculoskeletal disorders, burnout, and psychological suffering in Brazilian nursing workers: A cross-sectional study - Valim, Marília Duarte; de Sousa, Raymara Melo; Santos, Bruno da Silva; Alvim, André Luiz Silva; Carbogim, Fábio da Costa; de Paula, Vanessa Albuquerque; Pimenta, Fabiana Guerra; Junior, Aires Garcia dos Santos; Batista, Odinea Maria Amorim; de Oliveira, Layze Braz; Andrade, Denise; de Sousa, Álvaro Francisco Lopes (Belitung Raya Foundation, Indonesia, 2024)
Background: Musculoskeletal disorders (MSDs) pose a pervasive concern among nursing professionals due to the high physical workload. Simultaneously, the complex relationship between MSDs and mental health outcomes in this population remains an area of significant interest and importance. Objective: This study aimed to investigate the occurrence of MSDs and their relationships with burnout and psychological suffering within the nursing workforce. Methods: A cross-sectional study was conducted in 2020 involving 291 nursing professionals in Brazil. Standardized questionnaires were employed to gather information on MSDs, mental health outcomes, and pertinent work-related factors. Robust statistical analyses were conducted to ascertain the prevalence of MSDs, establish associations between MSDs and mental health outcomes, and delineate the influence of work-related factors on these associations. Statistical analysis was performed using the R software. Results: The study revealed a significant prevalence of musculoskeletal injuries (MSIs) among nursing workers, focusing on regions that include the lower back, upper back, neck, and shoulders. Individuals with MSIs in the lower back showed a marked increase in emotional exhaustion (p = 0.02), as did those with MSIs in the upper back (p <0.01) and depersonalization (p = 0.07). On the other hand, nursing professionals who reported MSIs in the neck and shoulders had considerably higher scores in emotional exhaustion (p <0.01 and p = 0.01, respectively) and depersonalization (p = 0.05 and p = 0.05, respectively). However, no significant correlations emerged between MSIs and depression or work-related factors. Conclusions: This study highlights the urgency of implementing proactive measures to prevent and manage MSDs within the nursing profession. Moreover, it emphasizes the critical need to enhance working conditions and provide robust support mechanisms to safeguard the mental health of nursing professionals.